Hyperthermia induced interleukin-12 gene therapy - Siddiqui, Farzan, author; Ullrich, Robert, advisor; LaRue, Susan M., advisor; Dewhirst, Mark, committee member; Avery, Paul, committee member (Colorado State University. Libraries, 2005)
Cytokine genes are the most widely and extensively studied immunostimulatory agents in cancer gene therapy. In several studies, interleukin-12 (IL-12) was found to be the most effective cytokine in inducing the eradication of experimental tumors, preventing development of metastases and eliciting long-term antitumor immunity. Local and systemic administration of IL-12 protein has been studied in murine models and in Phase I/II human trials. However, IL-12 protein therapy has been limited by dose-dependent toxicity. Local and efficient expression of IL-12 and other cytokine genes in tumors represents an alternative immunotherapeutic approach that may avoid systemic toxicity of recombinant cytokines. To achieve this goal of localizing gene expression, a heat-inducible adenoviral gene therapy vector with feline IL-12 being placed under the control of a heat inducible promoter was developed. The rationale for using this heat shock promoter (hsp70B) is that hyperthermia is most likely to be used as an adjuvant therapy with radiation and chemotherapy in the treatment of cancers. Heating the tumor leads to activation of the hsp promoter and subsequent local IL12 production. In this project the "adenovirus heat shock promoter feline interleukin-12" (AdhspfIL-12) gene construct was studied. In vitro studies were done to characterize the construct. Following that a phase I dose escalation trial was conducted in thirteen cats with spontaneously arising soft tissue sarcomas. The cats underwent radiation therapy to a total dose of 48 Gy in 16 fractions. Four-five days later the gene construct was injected intratumorally. Twenty-four hours post-injection the tumor was heated to a target temperature of 41°C for 60 minutes using a microwave applicator. Cats were treated at increasing dose levels of viral construct. Tumor expression of cytokines IL-12 and IFN-γ was quantitatively determined using real time PCR. The cats were monitored for hematologic and hepatic toxicity. In this trial, it was concluded that it is possible to limit the toxicity of interleukin-12 using the hyperthermia induced gene-therapy approach. The anti-angiogenic properties of IL-12 were quantitatively assessed using computerized image analysis in a mouse tumor model. A significant reduction in tumor vasculature was seen in the treated group of mice with limited systemic toxicity.
Keywords: oncology; genetics